Returns to Bidding and Target Finns in Hostile Takeovers: Some UK Evidence - Mohamad, Shamsher; Md Nassir, Annuar (1991)
This paper explores the returns to bidding and target firms in hostile takeovers and their combined wealth effects on the announcement of the offer in the UK. The findings reveal that bidder firms earn negative and significant abnormal returns, whereas target firms earn positive and significant abnormal returns. The gains to target firms more than compensate the losses suffered lry bidders as the combined gains are positive and significant. These findings are consistent with those documented in the US. The positive and significant combined gains imply that takeovers are wealth-creating investments, which is consistent with the notion that managers pursue takeovers to maximise wealth rather than size of theirfirm.